The Transition to Tertiary Education and Parental Background over Time - Riphahn, Regina Therese; Schieferdecker, Florian (Journal of Population Economics, 2012)
Using SOEP data (1984-2006) we analyze the role of parental background for transitions to tertiary education in Germany and answer three questions: (a) does the relevance of parental background shift from short-term (contemporary income) to long factors (ability, parental education) at higher levels of education? (b) Did the impact of parental background on participation in tertiary education change over time? (c) Are there different patterns by sex and region? We consider panel estimators with and without selectivity corrections and numerous robustness tests. Parental income significantly affects transitions to tertiary education. Its impact seems to have lost magnitude over time. We find no clear differences by sex, and larger parental income effects in West than in East German
WiSo-Import:2015-03-26:990
Keywords: Transformation; tertiary education; intergenerational transmission; human capital investment; education expansion; college entry